Efektivitas Penggunaan E-Learning Berbasis Multimedia dalam Meningkatkan Kemampuan Akademik Mahasiswa - Ratnah. S; Alfiana Damasinta (Academic Bright Collaboration, 2025)
Higher education has undergone a significant transformation in recent decades with the rapid adoption of digital technologies. One technology that plays an important role in this change is a multimedia-based e-learning system. This study aims to analyze the effectiveness of using multimedia-based e-learning in improving students' academic skills. Using a quantitative approach, this study involved students from various study programs in universities that use multimedia-based e-learning platforms. The results showed that the use of multimedia-based e-learning has a positive influence on improving material understanding, student engagement, and overall academic achievement. Specifically, students who used multimedia-based e-learning experienced a significant increase in their academic scores compared to students who used traditional learning methods. These findings indicate that multimedia-based e-learning technology can be an effective solution to improve the quality of learning in higher education, especially in an educational context that increasingly relies on digital technology.